PENGARUH PEMBERIAN GEL BINAHONG TERHADAP PENYEMBUHAN LUKA SAYAT - Deby Zulkarnain Rahadian Syah; Nofran Putra Pratama (Universitas Jenderal Achmad Yani Yogyakarta, 2020)
Background: Effective wound healing will reduce the costs incurred for treatment. Wound assessment, action and selection of treatment are carried out based on conditions and problems. Today's society prefers to do treatment by utilizing natural resources only on incision wounds given binahong leaves. Objective: Produces a binahong gel composition that heals cuts and minimizes infection in the incision. Methods: This research is included in inferential quantitative with parametric data. The mean difference test was then performed, followed by a paired t-test. Results: Administration of Na CMC On day 10 the mean wound closed was 18.83 cm with a standard deviation of 1.15. The administration of 1% binahong gel obtained an average wound healing area of 19.54 cm with a standard deviation of 0.18. The administration of 5% binahomg gel on the 6th day only showed wound healing with a T test value of 0.004 but on day 8 there was no additional wound closure with an average wound healing area of 6.36. The administration of 7.5% gel was known until the 10th day indicating that there was no wound healing. Giving Povidone iodine is known to be on the 8th day showing wound healing with an average wound healing of 6.65 cm. Conclusion: The 1% binahong gel was more effective in accelerating the healing of cuts in rats compared to the 5% and 7.5% binahong gel.